Physical oceanography during ALKOR cruise AL571 - Felix H Mittermayer; Jan Dierking; Hans-Harald Hinrichsen; Thorsten B H Reusch (PANGAEA, 2025)
Conductivity-temperature-depth profiles were measured using a Seabird SBE 911plus CTD during RV ALKOR cruise AL571. The CTD was equipped with duplicate sensors for temperature (SBE3plus), conductivity (SBE4) and oxygen (SBE43). Temperature, conductivity and oxygen sensors are calibrated by the manufacturer once a year before being mounted in January. They are used throughout the year and no post-cruise or in-situ calibration is applied. All other sensors are calibrated irregularly. Data were connected to the station book of the specific cruise as available in the DSHIP database.
In: Hinrichsen, Hans-Harald; Reusch, Thorsten B H; Dierking, Jan; Lehmann, Andreas (2025): Timeseries of physical oceanography in the Baltic Sea from 2011-2022 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.979407